Transcriptional analysis of sulfate reducing and chemolithoautotrophic sulfur oxidizing bacteria in the deep subseafloor. Issue 4 (8th April 2016) - Orsi, William D.; Barker Jørgensen, Bo; Biddle, Jennifer F.
Summary: Sulfate reducing bacteria (SRB) oxidize a significant proportion of subseafloor organic carbon, but their metabolic activities and subsistence mechanisms are poorly understood. Here, we report in depth phylogenetic and metabolic analyses of SRB transcripts in the Peru Margin subseafloor and interpret these results in the context of sulfate reduction activity in the sediment. Relative abundance of overall SRB gene transcripts declines strongly whereas relative abundance of ribosomal protein transcripts from sulfate reducing δ‐ Proteobacteria peak at 90 m below seafloor (mbsf) within a deep sulfate methane transition zone. This coincides with isotopically heavy δ 34 S values of pore water sulfate (70‰), indicating active subseafloor microbial sulfate reduction. Within the shallow sulfate reduction zone (0–5 mbsf), a transcript encoding the beta subunit of dissimilatory sulfite reductase ( dsrB ) was related to Desulfitobacterium dehalogenans and environmental sequences from Aarhus Bay (Denmark). At 159 mbsf we discovered a transcript encoding the reversely operating dissimilatory sulfite reductase α‐subunit ( rdsrA ), with basal phylogenetic relation to the chemolithoautotrophic SUP05 Group II clade. A diversity of SRB transcripts involved in cellular maintenance point toward potential subsistence mechanisms under low‐energy over long time periods, and provide a detailed new picture of SRB activities underlying sulfur cycling in the deep subseafloor.